RESTRUCTURING POST-GRADE SCHOOL OF SAN MARCOS UNIVERSITY - Arrarte Mera, Raúl Alberto (2010)
This research, funded by the Research Vice-Rector of our Mayor de San Marcos University, since 2009, is it has to propose the competent authority, the orderly restructuring of the Graduate School, which has currently 20 administrative in each faculty, which, according to 35 article of the Statutes, “is responsible for establishing policies of higher learning and to plan, regulate, supervise and coordinate Masters and PhD’s, rule has been governing since 1984, under Law No. 23733, together with its internal regulation procedures. As you can imagine that instruments were made for other time and place, without imagine the current global competition, which is shattering these organizations, being these nonprofit or services ones, as is the case of public universities. The results expecte to get are: the capacity of Postgraduate Units, increasing own revenue for the university, and simultaneously help to improve our institutional image contributing to the economic and social development, promoting the application of science and technology. The participating units will be, as shown, the postgraduate units: Administration, Accounting and Economics.